Implementasi Sistem Akuntansi Syariah dalam Asuransi Syariah di Indonesia - Muammar Khaddafi; Ajeng Retno Anggriani; Aulia Santika; Rahma Sari Utami; Fajri Ramadhan (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Industry in Indonesia plays an important role in ensuring transparency, accountability and compliance with sharia principles. This research aims to analyze the application of sharia accounting in sharia insurance companies in Indonesia, with a focus on financial reporting, revenue recognition, distribution of underwriting surpluses, and management of participant funds. The research method used is a qualitative descriptive approach through literature studies and interviews with related parties in several sharia insurance companies. The research results show that the implementation of sharia accounting in sharia insurance companies in Indonesia is in accordance with the Sharia Accounting Standards Guidelines issued by the Sharia Accounting Standards Board (DSAK) and the MUI National Sharia Council (DSN) Fatwa. Apart from that, the challenges faced include the need to increase human resources' understanding of sharia accounting and adapt to industrial developments. With the existence of a sharia accounting system that is transparent and compliant with sharia, it is hoped that it can increase public trust in sharia insurance in Indonesia.